HPLC Estimation of Pioglitazone in Formulations and in Pharmacokinetic Studies - Chowdary, K.P.R.; Galibsaheb, V. (Asian Journal of Chemistry, 2011)
A simple sensitive RP-HPLC method was developed and validated for the estimation of pioglitazone in bulk drug samples, its formulations and in plasma samples using RP C-18 column with UV detection at 269 nm. The mobile phase consists of a mixture of acetonitrile-water (60:40 % v/v) adjusted to pH 6.0 with 0.1 % v/v glacial acetic acid. The retention time for pioglitazone was 5.4 min. The intra-and inter-day coefficient of variation was less than 1.28 % showing high precision of the method. The method was highly accurate with a recovery in the range 99-100 %. The method was found suitable for estimating pioglitazone in plasma samples in pharmacokinetic studies.